Forage corn lines originated from the cross with Zea diploperennis I.: combining ability (Semiárida, 2020)
The forage corns are different from the grain corns in the development of the aereal part, filling grain, maintenance of the vegetative quality of the plant at the harvest moment, percentage of dry matter content and animal uptake. The corn silage was considered as a power food and its nutritious value based on the digestibility and other factors that affect It, and the parameter of the in vitro digestible dry matter of the complete plant and its component (leaf and spike) is used as a selection criterion. The forage value of the inbred lines were not only by its yield, but also through its capacity to produce superior hybrids combinations when crossing each to other. The general combining ability test determine that value. The heterosis of each cross represent the specific combining ability. The purpose of the present research was to study the general and specific combining ability of seven corn forage inbred lines with wild genes Introgression. The following variables were measured: leaf/stem relation, plant height, number of stems by plant, number of spikes by plant, diameter of the main stem and in vitro digestible dry matter. The hybrid 3 (760 x 779) show the greater value of specific combining ability and its component lines the greatest values of general combining ability in plant height, total and spike digestible dry matter production.
Keywords: corn; Zea diptoperennis I.; forage; combining ability; digestible dry matter